Intelligent Sorting System - Han, Kevin Soh Ping (Universiti Teknologi Petronas, 2004)
This project presents the design of an intelligent sorting system that integrates the pneumatic system and X-Y Robot as actuator, the Vision Sensor and the Programmable Logic Controller (PLC). This automated sorting system is designed with the main aim of reducing production time in manufacturing line that involves product sorting. In the industry, most sorting procedures are still done by humans which a re e rror prone and s low.With t he industrymoving t owards a pplication o f automation, this project is thus relevant. The main objective in constructing this project is to integrate system components into a sorting system using PLC, actuators which are the X-Y Robot and pneumatic system, and the Vision Sensor. A Human Machine Interface (HMI) is created for the PLC to be controlled via personal computer using Visual Basic. The scope ofthis project will be within PLC programming for system controller, pneumatic system design, setup and programming of the X-Y Robot, Vision Sensor control, Visual Basic HMI creation, and system design and integration of the whole system. Scope of literature review is within sorting system technology and approach. This project starts off with preliminary research and literature review followed by tools identification. Following steps include PLC parameter set-up and programming, actuator design and setup, vision controller setup and system integration. Each components of the system are tested individually and then integrated into a complete system. The system is then tested to operate in production mode to cater for industrial objective, which in this case to sort target objects. The project achieves all the main objectives underlines. Each major component is designed, developed and tested to be functioning well. The system integration comprises all the relevant components, all connected and communicating with each other. System integration is complete and successful. The project is completed within the time frame and serves the problem statement